2017
DOI: 10.1080/03079457.2017.1299922
|View full text |Cite
|
Sign up to set email alerts
|

Further investigations on the epidemiology of fowl typhoid in Brazil

Abstract: Salmonella Gallinarum (SG) causes fowl typhoid (FT), a disease responsible for economic losses to the poultry industry worldwide. FT has been considered to be under control in Brazil; nevertheless, since 2012 it has frequently been identified in poultry farming of several Brazilian states. The present study was aimed at assessing (i) the pathogenicity of a SG strain recently isolated from an FT outbreak affecting chickens of both white and brown layers; (ii) the transmission of SG through eggs and hatching; (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Our results suggest that these bvGA strains are probably circulating in the field for a long time, since the 1850s for 287/91 and since the 1950s for BR_RS12. These results are in agreement with previous reports that demonstrated more than one pattern of S. Gallinarum bvGA spreading in Brazil by ERIC-PCR and PFGE (Secundo de Souza et al, 2015;Celis-Estupiñan et al, 2017). Noteworthy, the results presented here are based only in two Brazilian strains, what might not be representative of all genetic diversity of bvGA field strains in the country.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results suggest that these bvGA strains are probably circulating in the field for a long time, since the 1850s for 287/91 and since the 1950s for BR_RS12. These results are in agreement with previous reports that demonstrated more than one pattern of S. Gallinarum bvGA spreading in Brazil by ERIC-PCR and PFGE (Secundo de Souza et al, 2015;Celis-Estupiñan et al, 2017). Noteworthy, the results presented here are based only in two Brazilian strains, what might not be representative of all genetic diversity of bvGA field strains in the country.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover they clearly clustered outside the SG9 bvGA sub-clade, so they did not originated from a recent event of SG9R vaccine reversion. Another studies also found genetic differences among the field strains circulating in Brazil and the vaccine strain (Secundo de Souza et al, 2015;Celis-Estupiñan et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been already postulated that the infection of D. gallinae could contribute to the reduction in the e cacy of antibiotic therapies during foci of FT [20], since the mites may offer a drug-free environment where S. Gallinarum can survive. The capability of mites to re-transmit the infection to chickens, along with the ubiquitous diffusion of D. gallinae, may provide an additional explanation for the limited e cacy of antibiotic treatments of FT, which has often been described [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, horizontal transmission contributes to fast dissemination within the flock. S. Gallinarum is horizontally transmitted and evidence points to a vertical dissemination route (Celis-Estupinan et al, 2017). Moreover, the infection causes high morbidity and up to 80% of mortality in young or adult chickens (Shivaprasad, 2000).…”
Section: Introductionmentioning
confidence: 99%